The Effect of Small Group Discussion Method to The Students’ Skill on Reading Descriptive Text at Grade Eight of SMP Negeri 7 Pematangsiantar - Pakpahan, Surya Ningsih; Napitupulu, Selviana; Sitanggang, Anita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is to find out whether the effect of small group discussion teaching strategy to the reading comprehension of grade eight students of SMP Negeri 7 Pematangsiantar. This research uses quantitative research with a quasi-experimental research methodology. The data from this study where collected and obtained through tests. The sample this research the VIII -8 as the experimental class and the VIII-9 as the control class. the test was carried out with pre-test and post-test to students using small group discussion teaching strategy. The research data and result findings of calculation, the research found the mean score in experimental class from pre-test to post-test are 52,66 and 79,83. than score in control class from pre-test and post-test are 46,83 and 57,16. the statistical hypothesis testing findings sample t-test are indicated ,at a level of significance of 5% (=0,05), that the t -test was 4,848 whereas t-table was 1.671 , or t-test>t-table .it can be concluded that the value of t-test was higher than the value of t-table .therefore, the alternative hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected .so, its mean that there is a significant effect of use small group discussion teaching method to the reading comprehension of grade eight students of SMP Negeri 7Pematangsiantar.